Patterns and predictors of self-medication behavior of weight loss medications: a cross-sectional analysis of social media influence and role of pharmacist intervention - Sarhan, Neven; Schaalan, Mona F.; El-Sheikh, Azza A. K. (Frontiers in Pharmacology, 2025)
BackgroundMisuse of weight-loss medicines, particularly those obtained via the internet and social media, raises critical concerns regarding patient safety, compliance, and risk of adverse drug reactions (ADRs).ObjectiveTo evaluate patterns of weight-loss medication acquisition, the influence of social media on drug use behaviors, the role of pharmacist recommendations, and the key predictors of self-medication and adherence.MethodsA cross-sectional survey was utilized to assess sources of procurement of weight loss drugs, impact of social media on drug use, and sufficiency of pharmacist counseling on safety and drug compliance.ResultsThe study revealed that 53% of participants reported using weight-loss medications without consulting a physician. Among them, 32% acquired the medications directly from a pharmacy without prescription and 15% online through social media platforms. A significant majority (68%) indicated being strongly influenced by social media, with Instagram (45%) and TikTok (30%) being the most cited platforms. Pharmacist consultation was associated with improved adherence (50% vs. 25%, p = 0.0001) and enhanced awareness of drug safety (55% vs. 30%, p = 0.0004). Logistic regression revealed that self-medication was significantly predicted by younger age (18–30 years, OR = 2.1, 95% CI: 1.3–3.4, p = 0.002), frequent social media use (OR = 1.8, 95% CI: 1.1–2.9, p = 0.01), limited access to healthcare services (OR = 2.5, 95% CI: 1.4–4.4, p = 0.001), and prior unsuccessful weight loss attempts (OR = 1.9, 95% CI: 1.2–3.1, p = 0.005). In contrast, medication adherence was positively associated with pharmacist recommendations (OR = 2.34, 95% CI: 1.45–3.76, p-value <0.001), younger age (OR = 1.8, 95% CI: 1.1–2.9, p = 0.004), better access to healthcare (OR = 2.8, 95% CI: 1.6–4.7, p-value <0.001), low social media dependence (OR = 2.2, 95% CI: 1.3–3.6, p = 0.002) and previous medication adherence experience (OR = 1.7, 95% CI: 1.1–2.8, p = 0.012).ConclusionFindings highlight a growing trend of social media-driven decisions regarding weight-loss medication use and the associated risks of unregulated online-purchases. Pharmacists play a crucial role in mitigating adverse outcomes by promoting drug safety and adherence. Policy efforts should focus on enhancing regulations of over-the-counter online sales, strengthening pharmacist-led patient education, and combating misinformation through evidence-based public health communication.